The floor is uneven. Limits and possibilities of local media development in a highly concentrated market - Acevedo, Jorge (2017)
The article presents the main features of the Peruvian radio and television market, and emphasizes the levels of concentration of advertising investment, frequency control and the regulatory framework tailored to the media groups. It also analyzes the possibilities of economic sustainability, growth and modernization of much of the local and regional media in a world context characterized by accelerated technological changes, and new habits and styles of consumption of the audiences. The paper also describes some strengths and strategies deployed by local and commercial radios and television stations with social development objectives (educational and community), aimed at enabling them to stay in the market and lay the groundwork for the complex transit towards the digitalization of production and distribution of multimedia content.